The Isolation and Characterization of Bacteriophages Infecting Avian Pathogenic Escherichia coli O1, O2 and O78 Strains - Kat R. Smith; Emmanuel W. Bumunang; Jared Schlechte; Matthew Waldner; Hany Anany; Matthew Walker; Kellie MacLean; Kim Stanford; John M. Fairbrother; Trevor W. Alexander; Tim A. McAllister; Mohamed Faizal Abdul-Careem; et al. (Viruses, 2023)
Avian pathogenic Escherichia coli (APEC), such as O1, O2 and O78, are important serogroups relating to chicken health, being responsible for colibacillosis. In this study, we isolated and characterized bacteriophages (phages) from hen feces and human sewage in Alberta with the potential for controlling colibacillosis in laying hens. The lytic profile, host range, pH tolerance and morphology of seven APEC-infecting phages (ASO1A, ASO1B, ASO2A, ASO78A, ASO2B, AVIO78A and ASO78B) were assessed using a microplate phage virulence assay and transmission electron microscopy (TEM). The potential safety of phages at the genome level was predicted using AMRFinderPlus and the Virulence Factor Database. Finally, phage genera and genetic relatedness with other known phages from the NCBI GenBank database were inferred using the virus intergenomic distance calculator and single gene-based phylogenetic trees. The seven APEC-infecting phages preferentially lysed APEC strains in this study, with ECL21443 (O2) being the most susceptible to phages (n = 5). ASO78A had the broadest host range, lysing all tested strains (n = 5) except ECL20885 (O1). Phages were viable at a pH of 2.5 or 3.5–9.0 after 4 h of incubation. Based on TEM, phages were classed as myovirus, siphovirus and podovirus. No genes associated with virulence, antimicrobial resistance or lysogeny were detected in phage genomes. Comparative genomic analysis placed six of the seven phages in five genera: Felixounavirus (ASO1A and ASO1B), Phapecoctavirus (ASO2A), Tequatrovirus (ASO78A), Kayfunavirus (ASO2B) and Sashavirus (AVIO78A). Based on the nucleotide intergenomic similarity (<70%), phage ASO78B was not assigned a genus in the siphovirus and could represent a new genus in class Caudoviricetes. The tail fiber protein phylogeny revealed variations within APEC-infecting phages and closely related phages. Diverse APEC-infecting phages harbored in the environment demonstrate the potential to control colibacillosis in poultry.